Efikasi Diri dan Berpikir Kritis Mahasiswa dalam Menulis Argumentatif - Angella Novitaningrum; Pipit Ertika Daristin (Mastery: Master of English Language Journal, 2025)
This study aims to examine the correlation between students’ self-efficacy and critical thinking in argumentative writing. Employing a quantitative correlational research design, the study investigates how students’ confidence in their writing abilities influences their capacity to construct logical, well-supported arguments. The findings reveal a strong positive correlation (r = 0.684, p < 0.01) between self-efficacy and critical thinking, suggesting that students with higher self-efficacy tend to engage more effectively in analytical reasoning and evidence-based argumentation. Additionally, a paired t-test indicates a substantial improvement in both self-efficacy (mean difference = 15.88, p < 0.001) and critical thinking (mean difference = 17.22, p < 0.001) following targeted writing interventions. These results highlight the importance of integrating self-efficacy-enhancing strategies into writing instruction to foster students’ confidence and critical thinking skills. Despite its contributions, the study acknowledges limitations related to sample size (N = 32) and external influencing factors. Future research should explore broader and more diverse student populations to validate these findings further.